Evaluating fresh beef quality attributes and the effect of postmortem time using bioelectrical impedance and meta-analysis - Najar Villarreal, Francisco (Kansas State University, 2021)
This study assessed the application of new technologies to optimize freshness quality of beef. Phase one investigated quality attributes of beef longissimus lumborum (LL) during retail display using surface and internal bioelectrical impedance analysis (BIA). Beef loins (N = 18) obtained from three commercial processors with three postmortem aging times (PMT; 27, 34, and 37 d), were cut into steaks and displayed aerobically at 0-4°C for 15 d. Microbiological populations, surface BIA (S-BIA), internal BIA (I-BIA), pH, instrumental color, proximate composition, and lipid oxidation were assessed. Steaks with a longer PMT had lower (P < 0.05) BIA values and shorter shelf-life during retail display than steaks with lower PMT. Steaks aged 27 d had higher (P < 0.05) BIA values on d 9 and 12 of display than steaks aged 34 and 37 d. Overall, BIA values increased on steaks during retail display possibly due to changes in structural proteins and poor water holding capacity (WHC) and were correlated (r = -0.64 -0.56, 0.70, and 0.69) with redness, yellowness, aerobic plate counts, and TBARS, respectively. The needles used for the I-BIA method are invasive and may translocate bacteria into the muscle; therefore, the use of S-BIA method is recommended. In phase two, the S-BIA method was used to assess postmortem chemical changes in normal and high-pH beef LL steaks during 9 d of simulated retail display at 0-4°C. Beef strip loins (N = 20; PMT = 14 d) obtained from a commercial processor were sorted into two treatments, normal-pH (5.61–5.64) and high-pH (6.2–7.0) and cut into steaks. Surface BIA, oxygen consumption (OC), metmyoglobin reducing activity (MRA), protein degradation, and WHC were assessed. Surface BIA was 20% higher (P < 0.05) for high-pH meat than steaks from normal-pH meat. Low correlations were found between S-BIA and OC, MRA, protein degradation, and WHC. Surface BIA is a method that could be used to separate normal- and high-pH strip loins with potential for rapid, in-plant use to identify dark-cutting beef; however, BIA is not as strongly correlated with changes in structural proteins after 14 d of aging and during retail display. For phase three, the color life threshold for LL and psoas major (PM) steaks during retail display and the effect of PMT on the display color life of LL and PM steaks using meta-analysis was determined. Lower bound estimates for a* as a borderline of LL and PM steaks were 20.24 and 20.99, respectively. The first 21 d PMT for LL steaks had the longest color life with 7 d of color life. Additionally, 22-28 and 29-65 d of PMT had 5 and 4 d, respectively, of color life for LL steaks. The borderline acceptability estimated for PM steaks with 0-7 d and 8-21 of PMT was 3 and 2 d of color life, respectively. Estimations from this meta-analysis demonstrate that using LL and PM subprimals having a PMT of 21 d or less and 7 d or less, respectively, would optimize retail display color life of aerobically packaged steaks.
Keywords: Beef; Bioelectrical impedance; Quality attributes; Color life; Meta-analysis